Two new species of Maiestas Distant (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with a new record from Australia - Fletcher, Murray J.; Dai, Wu (Zootaxa, 2018)
Two new species of the genus Maiestas Distant are described and illustrated from Australia, M. barrowensis n. sp. and M. viraktamathi n. sp. In addition, Maiestas webbi Zhang & Duan, previously known only from China, is recorded for the first time from Australia. A checklist of species from the Australian region and a key for their separation are provided.